Anticipatory Stress Responses and Immune Evasion in Fungal Pathogens. Issue 5 (May 2021) - Pradhan, Arnab; Ma, Qinxi; de Assis, Leandro J.; Leaves, Ian; Larcombe, Daniel E.; Rodriguez Rondon, Alejandra V.; Nev, Olga A.; Brown, Alistair J.P.
Abstract : In certain niches, microbes encounter environmental challenges that are temporally linked. In such cases, microbial fitness is enhanced by the evolution of anticipatory responses where the initial challenge simultaneously activates pre-emptive protection against the second impending challenge. The accumulation of anticipatory responses in domesticated yeasts, which have been termed 'adaptive prediction', has led to the emergence of 'core stress responses' that provide stress cross-protection. Protective anticipatory responses also seem to be common in fungal pathogens of humans. These responses reflect the selective pressures that these fungi have faced relatively recently in their evolutionary history. Consequently, some pathogens have evolved 'core environmental responses' which exploit host signals to trigger immune evasion strategies that protect them against imminent immune attack. Highlights: Fungal pathogens have evolved anticipatory behaviors that protect against imminent challenges in the host, such as immune attack. These anticipatory behaviors are reminiscent of core stress responses in model yeasts, in that they exploit one type of signal to mount protective responses against a second type of signal that is likely to follow the first. Anticipatory immune evasive responses differ between fungal pathogens, probably because these behaviors evolve rapidly depending on the nature of the selective pressures these fungi face and the energetic costs of the protective response. Anticipatory immune evasion represents a potential target for antifungal therapy as blocking this response exposes the fungus to immune clearance and can attenuate fungal virulence.